An up‐to‐date review of cardiac pacemakers and implantable cardioverter defibrillators. Issue 7 (2nd September 2021) - Kuang, Ronny JD; Pirakalathanan, Janu; Lau, Theodore; Koh, Daniel; Kotschet, Emily; Ko, Brian; Lau, Kenneth K
Abstract: Cardiac pacemakers are one of the most frequently encountered cardiac devices seen on chest imaging. They may include single or dual chamber pacemakers, automated implantable cardioverter defibrillators (AICD), biventricular pacemakers used for cardiac resynchronisation therapy (CRT), wireless CRT, leadless pacemakers, and subcutaneous implantable cardioverter defibrillators (SICD). This review aims to provide an up‐to‐date review on current implantable pacemaker and defibrillator devices.